Exporting Welfare: Social Policy as Foreign Policy in Brazil and the Global South - Anita Afriani Sinulingga; Asrinaldi Asrinaldi; Muhammad Saeri; Aidinil Zetra (Andalas Journal of International Studies (AJIS), 2026)
Bolsa Família is usually seen as one of Brazil’s leading anti-poverty programs. Its significance, however, has not remained within Brazil’s welfare system. Over time, the program also became part of Brazil’s external engagement, especially through the circulation of social policy expertise in South-South cooperation and global social protection debates. Drawing on Bolsa Família, this article examines how a social policy from the Global South can enter foreign policy practice. The study uses a qualitative case study and process-tracing approach, based on official documents, cooperation records, international organization reports, and relevant academic studies. The analysis identifies two connected patterns. When Brazil’s social policy agenda was closely aligned with domestic coalitions and foreign policy priorities, Bolsa Família circulated mainly through coordinated policy transfer, including technical cooperation, training, study visits, and policy artifacts. When this alignment weakened, the program did not disappear from global policy debates. Its circulation continued through indirect diffusion supported by international organizations, development banks, expert networks, and instrument constituencies. In this second pathway, learning, emulation, and selective adaptation became more visible than direct state orchestration.